2015
DOI: 10.5194/acp-15-1463-2015
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparing different devices for the investigation of ice nucleating particles using Snomax<sup>®</sup> as test substance

Abstract: Abstract. Seven different instruments and measurement methods were used to examine the immersion freezing of bacterial ice nuclei from Snomax ® (hereafter Snomax), a product containing ice-active protein complexes from nonviable Pseudomonas syringae bacteria. The experimental conditions were kept as similar as possible for the different measurements. Of the participating instruments, some examined droplets which had been made from suspensions directly, and the others examined droplets activated on previously g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
177
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(221 citation statements)
references
References 54 publications
20
177
0
5
Order By: Relevance
“…The ice nucleation efficiencies of 500-nm size-selected Snomax®, NX-illite, and SRFA are shown in Figure 7. Size-selected Snomax® and NX-illite have ξ-30 > -3, and all values are in agreement 10 with previous literature (Hiranuma et al, 2015;Wex et al, 2015). The ice nucleation efficiency of SRFA has been studied in the past (O'Sullivan et al, 2014;Wang and Knopf, 2011), but no previous measurements at -30 °C have been taken with an online ice nucleation counter.…”
Section: Effect Of Sp2 Laser On Mixtures Of Inp Proxies With Rbcsupporting
confidence: 75%
“…The ice nucleation efficiencies of 500-nm size-selected Snomax®, NX-illite, and SRFA are shown in Figure 7. Size-selected Snomax® and NX-illite have ξ-30 > -3, and all values are in agreement 10 with previous literature (Hiranuma et al, 2015;Wex et al, 2015). The ice nucleation efficiency of SRFA has been studied in the past (O'Sullivan et al, 2014;Wang and Knopf, 2011), but no previous measurements at -30 °C have been taken with an online ice nucleation counter.…”
Section: Effect Of Sp2 Laser On Mixtures Of Inp Proxies With Rbcsupporting
confidence: 75%
“…This reasonable agreement and consistency with a currently used method suggests that the MOUDI-DFT is a promising technique for measuring INP concentrations as a function of size in the atmosphere, although additional validation experiments are warranted. As different levels of agreement have been observed in past intercomparison studies depending on aerosol type Wex et al, 2015), additional intercomparison studies are needed with different aerosol types.…”
Section: Discussionmentioning
confidence: 99%
“…Lower FFs were measured in LACIS compared to the CSU-CFDC, and good agreement was found when particle residence times in the respective instruments were accounted for. Wex et al (2015) reported measurements on size-selected Snomax ® particles with seven instruments including LACIS and the Portable Ice Nucleation Chamber (PINC; Chou et al, 2011). Wex et al (2015) examined droplets formed on single particles and droplets taken from suspensions containing Snomax ® .…”
mentioning
confidence: 99%
“…Wex et al (2015) reported measurements on size-selected Snomax ® particles with seven instruments including LACIS and the Portable Ice Nucleation Chamber (PINC; Chou et al, 2011). Wex et al (2015) examined droplets formed on single particles and droplets taken from suspensions containing Snomax ® . The varying mass of Snomax ® per droplet or per particle that was examined by the different instruments was accounted for, and the results agreed within a factor of 3 below 263 K for all instruments.…”
mentioning
confidence: 99%
See 1 more Smart Citation